Current research progress of tranexamic acid in the management of patients with traumatic injuries in emergency settings - Zhang, Gengwei; Liu, Juan; Wen, Zhang; He, Jia; Chang, Haifeng (Frontiers in Disaster and Emergency Medicine, 2025)
IntroductionThe trauma is a leading cause of global mortality, with hemorrhage being a major contributor. Tranexamic acid (TXA), an antifibrinolytic agent, has shown promise in reducing blood loss and improving outcomes in trauma patients. Despite evidence from the CRASH-2 and CRASH-3 trials demonstrating its efficacy when administered within 3 h post-injury, tranexamic acid remains underutilized in clinical practice. This review aims to synthesize current evidence on TXA's efficacy, mechanisms, and clinical applications in the trauma management, identify research gaps, and propose future directions to optimize its use.MethodsA comprehensive literature search was conducted using PubMed, Embase, and Cochrane Library up to April 2025. Search terms included “tranexamic acid,” “trauma,” “hemorrhage,” and “emergency medicine.” Included studies were randomized controlled trials (RCTs), systematic reviews, meta-analyses, or observational studies evaluating TXA's efficacy, safety, or mechanisms in trauma patients. Case reports, editorials, and non-English studies were excluded. Data extraction and quality assessment were performed independently by two reviewers using the Cochrane Risk of Bias Tool and Newcastle-Ottawa Scale.ResultsThe review included 31 studies (15 RCTs, 10 systematic reviews, 6 observational studies). Early the TXA administration within 3 h post-injury significantly reduced mortality, with the CRASH-3 trial showing benefits within 8 h for traumatic brain injury. TXA inhibits plasminogen activation, stabilizing clot formation and reducing fibrinolysis, while also exhibiting anti-inflammatory properties. Intravenous TXA was more effective than oral administration. TXA reduced blood transfusions, reoperations, and blood loss in surgical settings. Limitations included variability in study designs, small sample sizes, and lack of long-term.DiscussionThe TXA is a critical intervention in the trauma management, reducing mortality and morbidity from hemorrhage. Early intravenous administration is preferred, and its anti-inflammatory properties may enhance recovery. However, underutilization in pre-hospital settings highlights the need for increased awareness and training. Future research should focus on individualized protocols, alternative administration routes, long-term safety, and combining TXA with other therapies to optimize trauma care.ConclusionThe TXA is a valuable therapeutic option in the trauma management, with significant potential to improve outcomes. Addressing current limitations and exploring new research directions will be essential to maximize its clinical benefits.